Effect of Electric Field Distribution on the Heating Uniformity of a Model Ready-to-Eat Meal in Microwave-Assisted Thermal Sterilization Using the FDTD Method - Hong, Yoon-Ki (Foods, 2021)
Microwave assisted thermal sterilization (MATS) is a novel microwave technology currently used in the commercial production of ready-to-eat meals. It combines surface heating of high-temperature circulation water with internal microwave heating in cavities. The heating pattern inside the food packages in a MATS process depends heavily on the electric field distribution formed by microwaves from the top and bottom windows of the microwave heating cavities. The purpose of this research was to study the effect of the electric field on 922 MHz microwave heating of ready-to-eat meals as they moved through the microwave chamber of a pilot-scale MATS system using the finite-difference time-domain (FDTD) method. A three-dimensional numerical simulation model was developed as a digital twin of the MATS process of food moving through the microwave chamber. The simulation showed that the electric field intensity of the MATS microwave cavity was greatest on the surface and side edge of the cavity and of the food. There was a strong similarity of the experimental heating pattern with that of the electric field distribution simulated by a computer model. The digital twin modeling approach can be used to design options for improving the heating uniformity and throughput of ready-to-eat meals in MATS industrial systems.